Characterization of the complete mitochondrial genome of Aulacophora indica (Insecta: Coleoptera: Chrysomeloidea) from Zhijiang. Issue 2 (2nd April 2020) - Wang, Hui; Bai, Yu; Li, Guoyong; Luo, Jianlin; Li, Can
Abstract: Aulacophora indica is one of the most important pests threatening the production of melon and vegetables. Samples of A. indica were collected from Zhijiang county and the mitochondrial genome was characterized (GenBank accession number MN162709). The mitogenome consists of a circular DNA molecule of 16, 246 bp, with an A/T bias of 78.54%. It comprises 13 protein-coding, 22 tRNA, and 2 rRNA genes. The protein-coding genes have typical ATN (Met) initiation codons and are terminated by typical TAN stop codons.